2021
DOI: 10.34297/ajbsr.2021.14.001976
|View full text |Cite
|
Sign up to set email alerts
|

Microbiome First Approaches in Pain Prevention and Management

Abstract: The Microbiome First Initiative aims to facilitate sustainable healthcare by focusing first and foremost on the human holobiont majority, the microbiome. Understanding how the human microbiome affects not only risk of disease but also human perceptions can help individuals thrive and pave the way for a healthy life course. Following a recent review of Microbiome First Medicine the context of health and safety, this present opinion article considers the role of the human microbiome, particularly the gut microbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 53 publications
(68 reference statements)
0
9
0
Order By: Relevance
“…infantis and related communities (a natural component of raw human breast milk) is key to human milk oligosacchrride (HMO) metabolism, difference in bile salt metabolism, changes in gut microbiome profiles, shifts in gut immune cells maturation/balance, reduced enteric inflammation, and protection against asthma and allergic diseases [4,54,55]. These findings support a major microbiome first type of application [1,5,6] for reducing the risk of entryway NCDs (e.g., asthma) that can lead to later-life multimorbidity and polypharmacy. One of the questions is whether raw cow's milk could mediate similar positive changes on the microimmunosome.…”
Section: Effects Of Raw Cow's Milk On the Microimmunosome And Risk Of Allergies And Asthma: Proof Of Conceptmentioning
confidence: 73%
See 2 more Smart Citations
“…infantis and related communities (a natural component of raw human breast milk) is key to human milk oligosacchrride (HMO) metabolism, difference in bile salt metabolism, changes in gut microbiome profiles, shifts in gut immune cells maturation/balance, reduced enteric inflammation, and protection against asthma and allergic diseases [4,54,55]. These findings support a major microbiome first type of application [1,5,6] for reducing the risk of entryway NCDs (e.g., asthma) that can lead to later-life multimorbidity and polypharmacy. One of the questions is whether raw cow's milk could mediate similar positive changes on the microimmunosome.…”
Section: Effects Of Raw Cow's Milk On the Microimmunosome And Risk Of Allergies And Asthma: Proof Of Conceptmentioning
confidence: 73%
“…The most recent study of epidemiologic data in the US [29] analyzed a dataset from the US CDC National Outbreak Reporting System (NORS) database for dairy outbreaks reported from 2005 to 2016 and summarized outbreaks of illness, hospitalizations, and mortality for raw and pasteurized milks and dairy products. Whitehead and Lake (authors' Table 1) [29] reported the following numbers of outbreaks, illnesses, hospitalizations, deaths, and deaths/1000 illnesses, respectively, for raw milk (152, 1735, 176, 2, and 1.2) and for pasteurized milk (6,1903,20,4, and 2.1) in this time period. Whitehead and Lake [29] reported that raw milk was associated with 2 deaths in the 12 year time period assessed, both in cases with significant co-morbidities, one with campylobacteriosis, the other with listeriosis.…”
Section: Risks: Contra-argument 821 Supportingmentioning
confidence: 99%
See 1 more Smart Citation
“…Two adverse outcomes received prior recent reviews within the Microbiome First series of papers. These concerned the capacity of the microbiome to regulate pain [95] and both the occurrence of substance abuse and the likelihood of successful withdrawal [20].…”
Section: Additional Outcomes Of Aces With Microbiota Regulationmentioning
confidence: 99%
“…As recently reviewed in Dietert and Dietert [95], microbiome adjustment including treatment with probiotics and prebiotics has the capacity to alter a variety of different types of pain. These alterations include changes in the perception of pain and in its persistence at various life stages.…”
Section: Painmentioning
confidence: 99%